A presença de instrumentos de percussão da música popular na música de concerto: estudo e performance de Íris para berimbau solo, de Alexandre Lunsqui; Concerto para pandeiro, de Tim Rescala; e Boreal III para chocalhos e eletrônica, de Guilherme Bertissolo - Mateus Espinha Oliveira (2015)
This work proposes to discuss the performance of concert music pieces written for popular music originated instruments. The focus of the work is on the implications for the performer of the use of instruments out of western music tradition in contemporary works. In this work are included three pieces, Íris, of Alexandre Lunsqui, Concerto para Pandeiro e Quatro Instrumentos, of Tim Rescala, and Boreal III, of Guilherme Bertissolo. I approach several issues inherent to the execution of these pieces, such as the technique of the instruments involved and the various possibilities and interpretive choices possible for each of them. For such, I seek a basis in the work of several performers recognized for their work with this instruments, both in the fields of popular music and concert music. Were also used methods, academic works, videos and books to approach the possibilities of each instrument. Besides that, there is a small musicological discussion around the re-contextualization of these instruments. Inside this project it was commissioned one piece, Boreal III, witch had the colaboration of the performer, who showed and commented diverse possibilities of the instruments used on it.